Buletin Fenomena - Abdi Fauji Hadiono (IAI Darussalam, 2016)
Mass media is one form of technological progress in the field of information and communication. The influence of mass media varies from each individual It also happens to students at boarding school Darussalam. The mass media is able to bring the students into new cultural patterns and begin to determine the mindset and behavior of santri. Therefore the role of mass media in positive influence is needed. This study focuses on whether the propagation content of the bulletin phenomenon affects the cognition of santri who read it. This research uses qualitative research methods. The population of this study is all the bulletin readers Phenomenon consisting of santri boarding school Darussalam. The data has been collected, tested its validity using triangulation technique method, source, and situation, then the data is analyzed. From the process of data analysis, it was found that the article Rubric contained propaganda in the bulletin Phenomenon affects the cognition of students who read it. Thus it can be concluded that the bulletin Phenomenon as one of the media information in Darussalam boarding school, affecting the cognition of the reader